Analysis of elderly people's travel behaviours during the morning peak hours in the context of the free bus programme in Beijing, China. (April 2019) - Zhang, Yongsheng; Yao, Enjian; Zhang, Rui; Xu, Hao
Abstract: With the development of social economy and health care technology, people are expected to live longer, and the world's population tends to be ageing. As one of the services for elderly people, the concessionary bus travel programme provides a kind of social welfare for elderly people, while peak-hour traffic pressures (e.g., traffic congestion, traffic injuries, and travel discomfort) faced by elderly people have been ignored. This paper attempts to help society create a better travel environment for elderly people by analysing their travel behaviours. Specifically, using household survey data from Beijing, the statistical analysis is used to paint a more detailed picture of daily travel experience of elderly people with regard to departure times, travel purposes, travel mode choices, etc. Then, a nested logit model is employed to interpret travel patterns of elderly people. The results show that the bus plays the most important role in motorized travel of elderly people. Furthermore, the free bus programme has induced only 4.85% of bus travel among elderly people, indicating that the programme has little effect on elderly people's bus choices. Based on the results of the analysis, several options are proposed in this paper to help society adapt to the changing demographics.